Learning Together: Social Work Students and Service Users Reflect Critically on Their Diverse Life Experiences - Böhler, Doris (Participatory Social Work: Research, Practice, Education, 2019)
In this chapter, the author introduces the concept of a project week where social work students study together with a diverse group of unemployed social work clients. This involves a learning approach as a formative research process, focusing on establishing and maintaining relationships and highlights communalities. The subject matter references a public forum organized by, “aqua muehle Vorarlberg”, during which students and service users present the results of their collective project week. The issues researched focus on unemployment, education, qualification, illnesses, discrimination and inclusion. A document analysis of learning journals together with records of feedback sessions and presentations of outcomes form the basis of this contribution. A series of new possibilities arise when groups form equally, leaving their “normalities” of familiar learning environments behind. The experiences are evaluated positively by the participants despite being described as exhausting, emotional and difficult. Role ambiguity contributes to a valuable experience of exchange.